A Design Thinking Approach to the Development of Digitalized Hotel Valet Services - Muhammad Al Makky; Tito Pandu Raharjo; Sheina Fathur Rahman; Rahmat Yasirandi (My University, 2025)
Technological advancements in Indonesia have brought numerous benefits, including to hospitality industries like valet parking. However, traditional valet services still rely on manual processes, leading to inefficiencies such as long wait times, miscommunication, and security concerns. This study focuses on developing a digital valet system using the Design Thinking Approach to address these challenges. The proposed prototype demonstrates strong acceptance, addressing user expectations and improving overall service efficiency. During the testing phase, the System Usability Scale (SUS) was employed with 50 participants who had experience in valet services, resulting in a score of 77.7. This score places the prototype in the “Good” grade and “Acceptable” category, indicating that the proposed system successfully addresses the functionality and requirements of its intended users. By modernizing valet operations, this study highlights the potential for broader adoption of digital solutions in the hospitality sector, ultimately improving guest experiences and operational effectiveness.
Keywords: Digital Marketing and Social Media; Consumer Retail Behavior Studies; Technology Adoption and User Behaviour